Hiding Names: Private Authentication in the Applied Pi Calculus - Fournet, Cédric; Abadi, Martın (International Symposium on Software Security (ISSS'02), 2002)
We present the analysis of a protocol for private authentication in the applied pi calculus. We treat authenticity and secrecy properties of the protocol. Although such properties are fairly standard, their formulation in the applied pi calculus makes an original use of process equivalences. In addition, we treat identity-protection properties, which are a delicate concern in several recent protocol designs.